The role of the Islamic religious organizations, some issues and considerations - Hasan Basri (Proceedings of AICS - Social Sciences, 2013)
In the country with the largest Muslim population, such as Indonesia, Islamic based religious organizations, such as pesantrens, have played a very significant role in providing  services for society. However, there are only a few studies that have examined the role of these kind of organizations in providing services for the community. As such, this article discusses some  issues and role played by religious based organization, specifically, Islamic religious organization. The paper starts by looking at the nature of religious organizations, and then followed by the brief of pesantrens. The  roles of Islamic religious organizations in Indonesia are also discussed.Keywords :Religious Organization, Islam, Pesantren